Survey on The Need of Labelling Tools Kit - Johan, Riche Cynthia; Ardiansah, Ardiansah; Suhardini, Dini (Universitas Pendidikan Indonesia, 2023)
Labelling books is one of the technical activities in the processing section of the library. This research is an initial study of the need to provide tools for labelling books, so as to provide convenience in the technical process of pairing bibliographic information in one book. The survey method was conducted on 21 librarians working in school libraries in West Java province. The results obtained were that every school librarian already had technical competence in processing library materials, and stated that they needed tools for the process of placing book labels. The librarians state that labelling is one of the library management activities to make the align collections or shelving easier for librarians so that collections can be accessible to library users. It is also beneficial for shelf reading to check if a library collection is improperly shelved and effectively locate missing or stolen books In addition to accessibility and shelf reading purposes, spine labels also give a sense of tidiness in the library because they are aligned and have the same size label used.